2021
DOI: 10.1101/2021.06.21.21259210
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrating a Polygenic Risk Score for Coronary Artery Disease as a Risk Enhancing Factor in the Pooled Cohort Equation is Cost-effective in a US Health System

Abstract: ImportanceThe pooled cohort equation (PCE) is used to determine an individual’s 10-year risk (low, borderline, intermediate, or high) of atherosclerotic cardiovascular disease (ASCVD) but it fails to identify all individuals at high risk. Those with borderline or intermediate risk require additional risk enhancing factors to guide preventive therapy decisions. Including a polygenic risk score (PRS) for coronary artery disease as a risk enhancing factor improves precision in determining the risk of ASCVD and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…A strong role of genetics or genomics in the disease etiology may even imply that patients or subjects with a high PRS benefit less from lifestyle changes, such as nutritional modification or smoking cessation, than those with a low PRS. Moreover, the advantages of earlier or more frequent screening using a reliable PRS-based panel will be able to reduce potential side effects such as life-threatening injuries occurring from radiation exposure, unnecessary screening, overdiagnosis, and neuro-degenerative distress after rupture symptoms [34].…”
Section: Discussionmentioning
confidence: 99%
“…A strong role of genetics or genomics in the disease etiology may even imply that patients or subjects with a high PRS benefit less from lifestyle changes, such as nutritional modification or smoking cessation, than those with a low PRS. Moreover, the advantages of earlier or more frequent screening using a reliable PRS-based panel will be able to reduce potential side effects such as life-threatening injuries occurring from radiation exposure, unnecessary screening, overdiagnosis, and neuro-degenerative distress after rupture symptoms [34].…”
Section: Discussionmentioning
confidence: 99%
“…118 Results of studies examining the added predictive value of a CVD PRS to such equations have been mixed. 77,78,[119][120][121] For example, in a recent largescale observational study of 352 660 individuals, Elliott et al 77 122,123 Likewise, several studies have directly shown that PRS perform better among participants <50 years. 122,124 In aggregate, we expect that as PRS methods are further developed and derivation GWAS cohorts increase in size and diversity, PRS will consistently demonstrate added predictive value to current risk equations, particularly in younger age groups.…”
Section: Clinical Utility Of Cvd Prs In Midlifementioning
confidence: 99%
“…(5-7.5%) or intermediate (7.5-20%) 10 year risk (BIR), additional Risk Enhancers can be used to further refine risk mitigation discussions between physician and patient, and PRSs have recently been proposed to aid clinical management of ASCVD in such discussions [25,28] while reducing healthcare costs from a payer's perspective [29]. We therefore sought to assess the potential for the multi-ancestry PRSs to be used as a discriminatory risk enhancing factor for CAD by using a two-fold increased risk threshold to identify individuals at high risk of CAD.…”
Section: Main Textmentioning
confidence: 99%
“…We show here that multi-ancestry CAD PRSs can play such a role by reclassifying significant proportions of individuals at increased risk of disease because of their genetics, but who are invisible and therefore missed by current ASCVD risk assessments, but who nevertheless go on to have disease. These PRSs are validated and calibrated on US populations and given their demonstrated cost-effectiveness [29,41] it is increasingly clear that they satisfy the criteria to be considered a Risk Enhancing Factor in the management of ASCVD risk.…”
Section: Main Textmentioning
confidence: 99%